Features of structural improvement of the cooking appliance for confectionery mass - Kobets, Anatolii; Puhach, Andrii; Volovyk, Iryna; Puhach, Vira (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the process of making confectionery masses using the example of boiling the jam mass with the introduction of pre-dried fruit and berry raw materials, followed by boiling in a sugar syrup solution on an advanced cooking device. A feature of the improved cooking apparatus is the elimination of intermediate heat carriers, ensuring mobility, and increasing the heat exchange surface. Additional heating of the stirring device increases the total heat exchange surface by 0.23 m2. The elimination of the steam component made it possible to install the device on a moving platform, thereby ensuring its use in small confectionery workshops. A method of jam production with the introduction of pre-dried fruit and berry raw materials and subsequent boiling in a sugar syrup solution is proposed. A feature is preliminary drying of raw materials in a vertical cylindrical IR dryer to 25...35 % SR at a temperature of 40...55 °С, grinding to 1.0...3.0 mm, with subsequent addition to sugar syrup. Boiling of the jam mass with the introduction of plant ingredients was carried out in the temperature range of 50...60 °С in the improved mobile design of the cooking apparatus to the content of 60...75 % SR, within 10...15 minutes. The set duration of output (620 s) to the stationary mode of cooking the jam mass at a temperature of 55 °С in the improved design of the cooking apparatus, which is 30 % less. The introduction of a stirrer design with a heating surface increases the usable heating surface by 0.23 m2, while the cooking time for jam, for example, is reduced by 26 %, and the specific heat consumption is reduced by 1.34 times. The use of an improved mobile device in the practical activities of enterprises of the industry will make it possible to reduce the time of cooking confectionery masses and improve operational indicators